PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KUALITAS AUDIT (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia) - Sukarno Sukarno (Universitas Pamulang, 2016)
This research aims to determine the effect of characteristic of audit committee consists of independence, competence, frequency of meeting, the size of the audit committee, tenure of audit committe, and multiple directorship of audit committee on the audit quality with the company size and leverage as control variables.In this research, Audit Quality measured on scale public accounting firm (KAP), with the proxied by Big Four and Non Big Four.Population of this research are manufacturing companies listed in Indonesia Stock Exchange in 2014. The procedure of sample selection using purposive sampling technique. The samples used were 79 companies. Methods of data analysis using descriptive statistics and logistic regression analysis.These results indicate that characteristic of audit committee and audit quality simultaneously was fit or match the data. The partial test results showed that independence and audit committee tenure have a negative significant effect on the audit quality. While competence and multiple directorship of audit committee members is not affected by the audit quality. However, frequency of meeting and the size members of audit committee has a positive significant effect on the audit quality.